2007
DOI: 10.1523/jneurosci.3908-06.2007
|View full text |Cite
|
Sign up to set email alerts
|

5-Hydroxytryptamine Induces a Protein Kinase A/Mitogen-Activated Protein Kinase-Mediated and Macromolecular Synthesis-Dependent Late Phase of Long-Term Potentiation in the Amygdala

Abstract: The amygdala is a critical site for the acquisition of learned fear memory in mammals, and the formation and long-term maintenance of fear memories are thought to be associated with changes of synaptic strength in the amygdala. Here we report that serotonin (5-hydroxytryptamine; 5-HT), a modulatory neurotransmitter known to be linked to learned fearful and emotional behavior, has dual effects on excitatory synaptic transmission in the basolateral amygdala. There is an early depression of synaptic transmission … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
65
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(68 citation statements)
references
References 79 publications
(109 reference statements)
3
65
0
Order By: Relevance
“…However, serotonin enhancement or activation of serotonergic receptors via specific agonists resulted in divergent effects in other studies. In some studies, serotonin or 5-HT receptor activation reduced or abolished LTP (Huang and Kandel, 2007;Kojima et al, 2003). This might be explained by the activation of different 5-HT receptor subtypes, the concentration of 5-HT agonists and antagonists, and different brain sites of action (Mori et al, 2001;Staubli and Otaky, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…However, serotonin enhancement or activation of serotonergic receptors via specific agonists resulted in divergent effects in other studies. In some studies, serotonin or 5-HT receptor activation reduced or abolished LTP (Huang and Kandel, 2007;Kojima et al, 2003). This might be explained by the activation of different 5-HT receptor subtypes, the concentration of 5-HT agonists and antagonists, and different brain sites of action (Mori et al, 2001;Staubli and Otaky, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Student's t-tests revealed no significant differences between conditions (p40.05). Impact of serotonin on neuroplasticity G Batsikadze et al animal studies have shown that serotonin can enhance LTP (Huang and Kandel, 2007;Kojic et al, 1997;Machacek et al, 2001;Mori et al, 2001;Ohashi et al, 2002;Park et al, 2012), block the stress-caused inhibition of LTP (Ryan et al, 2008) or block LTD . Activation of 5-HT receptors was furthermore shown to reverse LTD induction or convert it into LTP (Costa et al, 2012;Kemp and Manahan-Vaughan, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…However, activation of serotoninergic receptors also had opposing results on plasticity in other studies. Some studies have shown negative or no effect of serotonin on LTP induction (Edagawa et al, 1998;Huang and Kandel, 2007;Kojima et al, 2003;Normann et al, 2007;Sanberg et al, 2006), which can be explained by activation of different serotoninergic receptor subtypes, stage of brain development or dosage and frequency of application of 5-HT agonists or antagonists Park et al, 2012;Staubli and Otaky, 1994). To explore the reasons of such opposing results, future studies should address specific serotoninergic receptor subtypes, using different 5-HTreceptor agonist or antagonist drugs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, although task-or speciesrelated factors may contribute in the present spine growth pattern, the observation that spine density was increased at all dendritic loci in trained mice injected with SL65.0155 suggests that activation of 5-HT 4 Rs globally enhances connectivity and excitatory neurotransmission in learningactivated hippocampal circuits. Additional support for a role of 5-HT 4 Rs in the remodeling of experience-induced synaptic contacts comes from data showing that induction of late facilitation of synaptic transmission (L-LTP) in amygdala slices by local applications of the 5-HT 4 agonist RS67333 requires both protein synthesis and cytoskeletal rearrangements (Huang and Kandel, 2007). Thus, 5-HT 4 Rsmediated L-LTP elicits neuronal rewiring in the amygdala presumably favoring the storage of emotional memories in amygdalar circuits.…”
Section: Discussionmentioning
confidence: 99%